Efektivitas model pembelajaran SAVI (Somatic,Auditory,Visualization,Intellectually) Terhadap motivasi belajar PAI dan budi pekerti peserta didik - nursilawati; Ruswanto Ruswanto; Ais Istiana (Jurnal Bilqolam Pendidikan Islam, 2026)
This study aims to examine the effectiveness of the Somatic, Auditory, Visualization, Intellectually (SAVI) learning model on students’ learning motivation in Islamic Religious Education (PAI) at SMA Negeri 1 Tanjung Bintang. The research background was driven by the low level of students’ learning motivation, as indicated by limited active participation, minimal initiative to ask questions, and the low feedback indicators provided by teachers. The study employed a quasi-experimental design of the posttest-only control group, with two tenth-grade classes selected through simple random sampling. The experimental class received instruction using the SAVI model, which emphasizes multisensory engagement and interactive feedback, while the control class was taught through conventional methods. The research instrument consisted of a learning motivation questionnaire that had been tested for validity and reliability, with data analyzed using prerequisite tests (normality and homogeneity) and a t-test.The findings revealed that the implementation of the SAVI model had a significant effect on enhancing students’ motivation in learning PAI compared to conventional methods. Students in the experimental class demonstrated improvement in indicators such as perseverance, willingness to ask questions, and active participation, particularly in the aspect of feedback, which had previously been low. The novelty of this study lies in the application of the SAVI model in the context of PAI learning at the senior high school level, an area that has rarely been explored, thereby extending the existing literature by incorporating affective and religious dimensions.In terms of implications, this research contributes to the development of educational science by demonstrating that the multisensory SAVI approach is not only relevant for exact subjects but also effective in fostering students’ learning motivation and religious character. The findings provide valuable insights for teachers and schools in designing interactive, contextual learning and improving educational quality in the 21st-century learning era.